RESPON MASYARAKAT MISKIN TERHADAP PROGARM KARTU INDONESIA SEHAT DI DESA KEPENUHAN JAYA KECAMATAN KEPENUHAN HULU KABUPATEN ROKAN HULU - Guswita Rablika; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Healthis one of the basic human needs, because it is in a healthy state that humans can live, grow, prosper and be creative.Therefore every individual family and community has the right to receive protection from their health, and the state is responsible and regulates the right to live healthy lives, especially for the poor. The implementation of the indonesia Healthy Card (IHC) is part of the goverment’s efforts to provide comprehensive health services for people who fall into the category of the poor and the poor. The IHC targets are those belonging to these two categories, this is because the poverty rate in this country is still difficult to suppress. Poverty arises because the the community does not have the main abilities, has no income or hes adequate education, has poor health conditions, feel insecure, have low confidence in self-confidence. In all parts of Indonesia a healthy Indonesian card program is given to the community, one of them is in the upstream district of Rokan, Preciselyin the village of kepenuhan jaya, which receives the least healty Indonesian card. This is due to the uneven distribution of healthy Indonesian cards and the absence of socialization by related parties..Keywords:Poor Society, Indonesian Health card  (KIS).